Safety and effectiveness of oral hypoglycemic agents in women with gestational diabetes. Literature Review (2014)
Background: The aim of this article is to review the estimates of studies have proposed the use of oral hypoglycemic agents (HGO) for metabolic control in patients with Gestational Diabetes Mellitus (GDM), evaluating outcomes regarding effectiveness and safety: breast, fetal, obstetric and neonatal outcome; comparing these outcomes with insulin therapy and among themselves, in order to contribute to understand the risks and benefits of using HGO in the current management of GDM. Materials and methods: A review was carried out in the literature recorded in four databases: PubMed, Ovid, Cochrane and ProQuest, between December 2007 and December 2012. Results: Clinical trials (n = 7), meta-analysis (n = 2), systematic reviews (n = 2), cohort studies: (n = 3), cost analysis study (n = 1) and ranked 15 items were included. Conclusion: HGO provide adequate control of maternal glycemia and perinatal results comparable insulin therapy, and they should be considered as effective and safe option in the treatment of GDM.